Umami Ingredient: Flavor enhancer from shiitake (Lentinula edodes) byproducts - Harada-Padermo, Samara dos Santos (2020)
An alternative use of shiitake stipes, usually treated as waste, was proposed for the production of a powder ingredient, rich in umami compounds, aiming its application in food. The extraction of umami compounds was optimized through the Response Surface Methodology (RSM), in order to obtain an extract with high umami taste intensity. From the optimized condition, a comparative analysis of shiitake stipes dehydration method was performed. Stipes were dehydrated by hot air drying (HD) and freeze drying (FD), submitted to extraction and the umami compounds in the extracts were compared. The comparative analysis showed that the 5′ - nucleotides are more sensitive to prolonged heating, while the release of free amino acids (FAA) was favored by hot air drying. The HD samples extract showed higher Equivalent Umami Concentration (EUC). The spray drying of the HD samples extract allowed the production of a newly powder ingredient rich in umami compounds (Umami Ingredient) that can be applied in diverse food matrices. Due to the presence of umami compounds, Umami Ingredient can be a potential alternative to help in the process of sodium reduction by enhancing food flavor.